The “dance” of reconciliation: Understanding the complex steps in a reconciliatory pedagogy using an oral history assignment (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
This article is about understanding the challenges and successes of a reconciliatory pedagogy with second-year student history teachers, eleven years after South Africa’s Truth and Reconciliation Commission (TRC) was established. While the TRC report stated that it started South Africa on the journey towards reconciliation, it never claimed that it was able to achieve this goal, although its legacy continues to affect the way reconciliation unfolds in this country. Education plays an important role in addressing the effects of conflict on the second generation, but the contribution history education could make has largely been ignored (Cole & Barsalou, 2006). Using eight interviews with student history teachers, which reflected on an oral history assignment at the University of the Witwatersrand, this article focuses on understanding the complex steps involved in a reconciliatory pedagogy. Applying the image of the “dance” of reconciliation (Lederach 1999) and selected examples from the TRC to the data from the interviews, helped to contextualise the students’ responses in relation to the main ideas that inform reconciliation. This provided insights into the twists and turns involved in this difficult process, and how it affected relationships between the first and second generations. It also allowed me the opportunity to reflect on my own practice as a history teacher educator.
Keywords: “Dance” of reconciliation; Reconciliatory pedagogy; Student history education; Narrative inquiry; Oral history; South Africa’s Truth and Reconciliation Commission